AHP and SAW Based Decision Support for Indonesia Smart Program Beneficiaries - Imam Halim Mursyidin; Doni Prasetyo; Dede Irawan (bit-Tech, 2025)
The Indonesia Smart Program (PIP) is a government initiative that provides cash assistance to help underprivileged children access education. SD Negeri Cikuya 4, located in the Solear subdistrict, is one of the schools implementing PIP. However, the school has struggled to decide which students should receive the aid because there is no systematic weighting of the criteria and the scoring has been subjective. This study asks whether combining AHP and SAW can produce objective weights and a transparent ranking of recipients. To address this, we developed a Decision Support System (DSS) that uses the Analytical Hierarchy Process (AHP) to set the relative weights for six criteria: ownership of KIP/KKS/PKH/SKTM, student active/enrollment status, child status, parents’ occupation, parents’ income, and number of dependents. The pairwise-comparison consistency ratio met the validity threshold (CR = 0.0803 < 0.10), indicating consistent judgments. These AHP weights were then integrated into Simple Additive Weighting (SAW) to normalize scores, calculate preference values, and prioritize eligible recipients. The results show that the selection process becomes more objective, transparent, and systematic than the traditional manual approach. A system quality test using ISO 9126 produced an average score of 86.67% (“Very Good”). This provides a replicable decision framework at the school level to improve the targeting of PIP assistance.